1961
DOI: 10.1161/01.res.9.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation of Ventricular Response in Atrial Fibrillation

Abstract: The autocorrelation function of the ventricular electrocardiogram was calculated on an IBM-650 computer. The resulting function can lie fitted by an exponential-cosine function. This result is typical for a mixture of periodic and unperiodic events. For different patients, various degrees of periodicity were put in evidence by this method on a quantitative basis; the ventricular response was never completely irregular. In all cases investigated so far, the period that corresponds to the periodic component of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1965
1965
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Of the total group of 66 patients with AF, the 3D plots indicated the presence of clustering in 31 patients (47%), leaving 35 patients in whom no clustering was demonstrable. As such, our study supports the work by previous investigators 7–10 that a certain degree of “hidden” clustering of RR intervals may be present in AF. Moreover, based on our data, it appears that clustering is not a rare phenomenon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the total group of 66 patients with AF, the 3D plots indicated the presence of clustering in 31 patients (47%), leaving 35 patients in whom no clustering was demonstrable. As such, our study supports the work by previous investigators 7–10 that a certain degree of “hidden” clustering of RR intervals may be present in AF. Moreover, based on our data, it appears that clustering is not a rare phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…However, controversy exists whether the ventricular rhythm in AF is truly random. Although some investigators contend that ventricular rhythm in AF is indeed truly random, 6 others, using a variety of mathematical techniques, have shown that a certain degree of “patterning” (or “clustering”) may be present 7–10 . This in turn suggests a certain degree of organization of atrial fibrillatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…These controversies arise from the fact that different groups of investigators have found differing patterns of ventricular irregularity in patients with atrial fibrillation (2)(3)(4)(5)(6) . Our findings (6) indicate that the ventricular rhythm is random, while others have produced evidence for a measurable amount of interdependence between successive R-R intervals ( time between R waves of two successive QRS complexes).…”
mentioning
confidence: 99%
“…Progressive amplification by increases in atrial rate led to maximal effects during atrial fibrillation. Although several models have been proposed to account for the ventricular response to atrial fibrillation, [16][17][18][19][20]22,[30][31][32][33][34][35][36][37][38][39][40] our results can be understood by the classic mechanisms proposed by Langendorf16 and extended by others. [17][18][19][20]22,36 It is assumed that rapid, irregular atrial impulses penetrate the AV node with variable strength from multiple directions.…”
Section: Discussionmentioning
confidence: 52%